SCIENTOMETRIC ANALYSIS OF BIG DATA ANALYTIC AND HALAL SUPPLY CHAIN MANAGEMENT - Kuncorosidi Kuncorosidi; Daeng M. Nazier; Riznaldi Akbar; Eddy Prabowo (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2024)
This study aims to conduct a scientometric analysis of "Analitika Big Data in Halal Supply Chain Management" between 2018 and 2024 In this study, keyword analysis and citation analysis were carried out using Dimensions and VOS viewer software, as well as identifying the most commonly used keywords. In addition, this study also conducted a co-author analysis, co-citation analysis, and analysis of countries and organizations involved in the study. The keyword analysis results show that the most discussed topics in this field are information management, the Internet of Things (IoT), sustainable development, and competition. The countries most active in Analitika Big Data in supply chain management are Malaysia, The United Kingdom, India, Italy, China, the United States, Turkey, Saudi Arabia, Egypt, Germany, New Zealand, Australia, and Bangladesh. This study recommends a thorough Scientometrics Analysis as a future research direction. In addition, the importance of the application of evolutionary computing and interdisciplinary work in dealing with practical problems related to big data was also identified. This digest provides an overview of the study's objectives, methods, and main findings "Scientometric Analysis of Big Data Analytic in Supply Chain Management. The research provides insight into research trends, country and journal contributions, and recommendations for future research in Analitika Big Data in supply chain management